A THEORETICAL APPROACH ABOUT CYBER SPACE AND SECURITY POLICY - GÜNTAY, Vahit (Cyberpolitik Journal, 2017)
The interest about the cyber security and cyber space is increasing day by day and developing power concept is discussed with its own integrity in cyber area at International Relations discipline. After the Cold War with its bipolar system, borders were removed in minds and multiple security concept shaped with its more dynamic qualities. While it is not possible to make sentence about the concept of security, it is challenging to evaluate cyber security concept in offensive-defensive strategy or establish a policy. The dimension of the security dilemma is affected excessively by technological developments and cyberpolitics become more complicated in global risk society. The diversity of approach strengthens the states but it carries the security perception to utopic dimensions in the common peace concept. In this study, international relations discipline has been examined with its different aspect in which cyber security added a new dimension as a perception. Also it is very problematic issue to construct an approach, the concept of the study is to try an essay about cyber security and International Relations.